2018
DOI: 10.1016/j.virol.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of HIV-infected T-cells by SWATH mass spectrometry

Abstract: Viral pathogenesis results from changes in host cells due to virus usurpation of the host cell and the innate cellular responses to thwart infection. We measured global changes in protein expression and localization in HIV-1 infected T-cells using subcellular fractionation and the Sequential Window Acquisition of all Theoretical Mass Spectra (SWATH-MS) proteomic platform. Eight biological replicates were performed in two independent experimental series. In silico merging of both experiments identified 287 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Virus replication/production was quantified by a reverse transcriptase (RT) assay as described previously (DeBoer et al ). Triplicate 10 μL of supernatant were assayed per timepoint.…”
Section: Methodsmentioning
confidence: 99%
“…Virus replication/production was quantified by a reverse transcriptase (RT) assay as described previously (DeBoer et al ). Triplicate 10 μL of supernatant were assayed per timepoint.…”
Section: Methodsmentioning
confidence: 99%
“…Vimentin has been found to interact with hepatitis C virus (HCV) core protein, which regulates its expression, impacting virus replication [157]. Vimentin is also important for efficient infection by HIV [158,159], through mechanisms that are not yet well understood. Interestingly, DeBoer et al [158] also found that abundance of vimentin is increased in the cytoplasmic and membrane fractions in infected cell cultures.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Vimentin is also important for efficient infection by HIV [158,159], through mechanisms that are not yet well understood. Interestingly, DeBoer et al [158] also found that abundance of vimentin is increased in the cytoplasmic and membrane fractions in infected cell cultures. Conversely, vimentin expression has been observed to be negatively affected by virus infection in some cases.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Vimentin has been found to interact with hepatitis C virus (HCV) core protein, which regulates its expression, impacting virus replication [136]. Vimentin is also important for efficient infection by HIV [137,138], through mechanisms that are not yet well understood. Interestingly, DeBoer et al (2018) also found that abundance of vimentin is increased in the cytoplasmic and membrane fractions in infected cell cultures.…”
Section: Viral Infectionsmentioning
confidence: 99%